An Evaluation of Incident Chronic Kidney Disease Across Ontario and Healthcare Utilization Through Predictive Risk Equations - Dhaliwal, Shan (Université d'Ottawa | University of Ottawa, 2026)
Chronic Kidney Disease remains a common, progressive condition that affects approximately one-tenth of the adult population. Despite its marked prevalence, there has yet to be a true estimation of its incidence within Ontario, Canada. The first objective of this thesis is to evaluate the incidence of early-stage CKD across Ontario and determine which groups are most at-risk. The implications of these results we hope will help determine resource allocation for policy makers and raise awareness for those who have a higher likelihood of developing CKD. The second objective will be to identify those who are at risk of CKD using a risk equation and determine their healthcare utilization, specifically investigating primary care access, specialist referrals, disease monitoring, and prescription management, across risk categories. These results will describe how those at higher risk of CKD are being evaluated and managed throughout their healthcare journey.
Keywords: Incidence; Chronic Kidney Disease; Healthcare Utilization; Predictive Risk Equations